Rationality and Prescribing Pattern of Antimicrobials on Female Lower Genital Tract Infection in a Tertiary Care Hospital of Odisha - Ginia Agasti; Rasmita Jena; Dipti rani Rath; Trupti Rekha Swain; Goutam Ghosh; Durga Madhab Kar (Journal of Global Pharma Technology, 2019)
Objective: Current study is based on the pattern analysis of various antimicrobial prescriptions for the treatment of female lower genital tract infection and its validation of rational use in a tertiary care hospital of Odisha. Methods: The current prospective investigation was carried out in outpatient department of Obstetrics and Gynaecology department at a tertiary care hospital over a period of six months. A suitable data collection was carried out from female lower genital tract infection patients who were of 11-55 years of age group. Results: The study result found that most commonly prescribed antimicrobials were antifungal (azoles derivatives) and its combination with other antimicrobials. The other antimicrobials include, topical (8.4%)/single antimicrobial oral (2.8%)/ combination (intravaginal as well as oral- 50%) followed by other antimicrobials like linozolid (4.8%). Our study reveals that, antifungal agents are the most common antimicrobial drugs prescribed on the basis of laboratory diagnosis report, which revealed that, staphylococcal infection in majority of the patients (42%). Conclusion: Hence, present study shall definitely provide a small initiative towards control of emergence of antibacterial resistance, its side effects and cost of therapy worldwide.Keywords: Prescribing pattern, Antimicrobials, Lower genital tract infection, Tertiary care hospital.